Simultaneous Real-Time Measurement of Isoprene and 2-Methyl-3-Buten-2-ol Emissions From Trees Using SIFT-MS - Lehnert, Ann-Sophie; Perreca, Erica; Gershenzon, Jonathan; Pohnert, Georg; Trumbore, Susan E. (Frontiers in Plant Science, 2020)
The C5 hemiterpenes isoprene and 2-methyl-3-buten-2-ol (MBO) are important biogenic volatiles emitted from terrestrial vegetation. Isoprene is emitted from many plant groups, especially trees such as Populus, while emission of MBO is restricted to certain North American conifers, including species of Pinus. MBO is also a pheromone emitted by several conifer bark beetles. Both isoprene and MBO have typically been measured by proton-transfer reaction mass spectrometry (PTR-MS), but this method cannot accurately distinguish between them because of their signal overlap. Our study developed a method for using selective ion flow tube mass spectrometry (SIFT-MS) that allows simultaneous on-line measurement of isoprene and MBO by employing different reagent ions. The use of m/z(NO+) = 68 u for isoprene and m/z(O2+) = 71 u for MBO gave minimal interference between the compounds. We tested the suitability of the method by measuring the emission of young trees of Populus, Picea and Pinus. Our results largely confirm previous findings that Populus nigra, Picea glauca and Picea abies emit isoprene and Pinus ponderosa emits MBO, but we also found MBO to be emitted by Picea abies. Thus SIFT-MS provides a reliable, easy to use, on-line measuring tool to distinguish between isoprene and MBO. The method should be of use to atmospheric chemists, tree physiologists and forest entomologists, among others.